2020
DOI: 10.1007/s10529-020-03065-y
|View full text |Cite
|
Sign up to set email alerts
|

Low-quality animal by-product streams for the production of PHA-biopolymers: fats, fat/protein-emulsions and materials with high ash content as low-cost feedstocks

Abstract: Objective The rapid accumulation of crude-oil based plastics in the environment is posing a fundamental threat to the future of mankind. The biodegradable and bio-based polyhydroxyalkanoates (PHAs) can replace conventional plastics, however, their current production costs are not competitive and therefore prohibiting PHAs from fulfilling their potential. Results Different low-quality animal by-products, which were separated by thermal hydrolysis into a fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 30 publications
0
30
0
Order By: Relevance
“…MSM for shake flask screening and bioreactor cultivations contained the FPE as the sole carbon and nitrogen source. FPE was composed as previously reported: 53% dry matter, 38% fat with 49% free fatty acids, 11% total protein content and melting point of at least 100°C (Saad et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MSM for shake flask screening and bioreactor cultivations contained the FPE as the sole carbon and nitrogen source. FPE was composed as previously reported: 53% dry matter, 38% fat with 49% free fatty acids, 11% total protein content and melting point of at least 100°C (Saad et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study, such an FPE was identified as a potential feedstock for PHA production with R . eutropha in a shake flask screening (Saad et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The use of engineered microbial strains was also reported for the production of poly(3‐hydroxybutyrate‐co‐3‐hydroxyhexanoate) (P(HB‐co‐HHx)) copolymer from fish or pork fat (Saad et al., 2021). The animal byproducts were treated by thermal hydrolysis, and a maximal yield of 90 wt% PHA per cell dry weight was produced in shake flask cultivations.…”
Section: Waste From Foods As a Carbon Source: Bioplasticsmentioning
confidence: 99%
“…Meat industry generates approximately 100 million tons of animal by-products annually; for example, around 30% of pig live weight and 40% of cattle live weight end up as animal by-products. 1 Some of these animal by-products, such as trimmings and internal organs, are good sources of animal proteins, minerals (mostly iron and phosphorus) and vitamins. 2 Enzymatic hydrolysis is a widely applied method in the food and pharmaceutical industries to valorise by-products because it is fast, controllable and sustainable without reducing the nutritional value of the materials.…”
Section: Introductionmentioning
confidence: 99%
“…Meat industry generates approximately 100 million tons of animal by‐products annually; for example, around 30% of pig live weight and 40% of cattle live weight end up as animal by‐products 1 . Some of these animal by‐products, such as trimmings and internal organs, are good sources of animal proteins, minerals (mostly iron and phosphorus) and vitamins 2 …”
Section: Introductionmentioning
confidence: 99%